GRAMMAR TEACHING CHALLENGES IN MALAYSIAN HIGHER EDUCATION - Abdul Rahman, Ayuni Madarina; Ismail, Hazian; Ismail, Norkatyniy (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Teaching grammar within the language education landscape presents an enduring challenge for educators. The ongoing debate surrounding the effectiveness of explicit versus implicit instruction underscores the dynamic nature of pedagogical practices in this field. To address this debate and gain a comprehensive understanding of grammar instruction, this research focuses on exploring the drawbacks of both approaches within educational institutions. By examining the practical implications of explicit and implicit instruction, this study aims to provide insights into their application in real-world teaching contexts. Through qualitative research method, faculty members from private institutions in Peninsular Malaysia were engaged in interviews, enabling them to share their first-hand experiences and perspectives on implementing these instructional methods. The findings from these interviews revealed three main challenges faced by educators when teaching grammar. Among these challenges, time constraints emerged as a significant hurdle, impacting the quality and depth of grammar instruction provided to students. Moreover, the research reveals further insights into the diverse requirements and preferences of students, as well as the diverse teaching approaches employed by instructors. Such insights are crucial for guiding the creation of personalized instructional approaches that meet the specific needs of learners in higher education contexts.